2019
DOI: 10.1177/1550059419856968
|View full text |Cite
|
Sign up to set email alerts
|

EEG Findings in Posterior Reversible Encephalopathy Syndrome

Abstract: Introduction. Posterior reversible encephalopathy syndrome (PRES) is a relatively common cause of encephalopathy in the hospital setting, and the EEG findings have not been well described. The purpose of this study was to review the EEG findings in a series of patients with PRES. Methods. We retrospectively reviewed our electronic medical record database to identify patients who received a diagnosis of PRES at Tampa General Hospital from January 2016 to October 2017. The diagnosis of PRES was suspected on clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Previously published data on EEG findings in PRES indicate that most of the patients exhibit diffuse slowing of cortical waves. 10,11 In a recent retrospective trial, Murray et al 12 showed that EEG findings in PRES can range from normal to generalized periodic discharges. PRES is a rare condition, and the majority of the findings are based on small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published data on EEG findings in PRES indicate that most of the patients exhibit diffuse slowing of cortical waves. 10,11 In a recent retrospective trial, Murray et al 12 showed that EEG findings in PRES can range from normal to generalized periodic discharges. PRES is a rare condition, and the majority of the findings are based on small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…EEG is a commonly used assessment tool in patients with encephalopathy and seizures. Specific EEG patterns have been associated with various conditions, such triphasic waves in toxic/metabolic abnormalities and the extreme delta brush pattern in autoimmune encephalitis (43). However, to the best of our knowledge, no specific pattern has been consistently reported for EEGs in patients with PRES, and the reported origin of seizures on EEG may not correlate with MRI findings (43,44).…”
Section: The Differences In Clinical Presentation May Suggest Differe...mentioning
confidence: 93%
“…Specific EEG patterns have been associated with various conditions, such triphasic waves in toxic/metabolic abnormalities and the extreme delta brush pattern in autoimmune encephalitis (43). However, to the best of our knowledge, no specific pattern has been consistently reported for EEGs in patients with PRES, and the reported origin of seizures on EEG may not correlate with MRI findings (43,44). In a study conducted on adult oncology patients with PRES, the most common EEG finding on a standard recording was diffuse slowing (44).…”
Section: The Differences In Clinical Presentation May Suggest Differe...mentioning
confidence: 99%
“…With the development of high-throughput EEG technology and the intelligence of EEG data analysis [5], retrospective analysis of high-throughput EEG data is expected to perform localization analysis of cerebral neurological deficits [6]. In conclusion, EEG-based cerebral neurasthenia detection will develop in the direction of quantitative, fine, and accurate localization, and the fatigue detection ability and alertness assessment credibility of drivers will be continuously improved [7].…”
Section: Introductionmentioning
confidence: 99%